THE IMPACT OF MICROPLASTICS ON MALE FERTILITY - Melania Czapla; Kacper Szada-Borzyszkowski; Konstancja Owczarenko; Bartosz Wróbel; Lena Wójcik; Krzysztof Gadzalski; Michał Filipski (International Journal of Innovative Technologies in Social Science, 2026)
Male infertility represents a growing global health concern, accounting for more than half of all infertility cases, while its environmental determinants remain insufficiently explored. Over recent decades, a marked decline in semen quality has coincided with the rapid expansion of plastic production and the widespread presence of microplastics and nanoplastics in the environment. This narrative review aims to synthesize current evidence on the impact of micro- and nanoplastic exposure on the male reproductive system, identify key mechanisms of reproductive toxicity, and highlight gaps requiring further investigation. A comprehensive literature search was conducted using PubMed, Scopus, Web of Science, and Google Scholar, focusing on experimental, epidemiological, and review studies addressing microplastics, male fertility, and reproductive toxicity. Available data indicate that microplastics can accumulate in testicular tissue and adversely affect spermatogenesis through multiple pathways, including disruption of the blood–testis barrier, oxidative stress, chronic inflammation, endocrine dysregulation, and structural damage to Sertoli and Leydig cells. These alterations are consistently associated with impaired sperm concentration, motility, morphology, and hormonal balance in experimental models. Although human data remain limited, emerging evidence suggests that lifelong, low-dose exposure may contribute to declining male reproductive potential. The review also discusses preventive strategies and emerging therapeutic approaches aimed at mitigating microplastic-induced reproductive damage. Collectively, current findings support microplastics as a relevant and potentially modifiable environmental risk factor for male infertility.